Peran Guru pada Pembelajaran Mata Pelajaran Aqidah Akhlak dalam Menanamkan Nilai-Nilai Keagamaan Bagi Siswa MTs Sunan Ampel Krejengan Kab. Probolinggo - Hayani, Nur; Fathullah Rusly; Taufiqurrohman Rifa'i (An Naba, 2023)
This study's goal was to describe how teachers in the Akidah Akhlak subject helped MTS sunan ampel krejengan students develop strong religious values. This study uses a qualitative descriptive research methodology with specific steps. The findings demonstrated how important it was for teachers to teach Aqidah Aqidah classes to MTS students in order to establish religious values, given the modern environment's substantial impact on kids. The lecture technique and habituation method are the methods the teacher uses to teach aqeedah morals. The method for understanding the significance of teaching pupils about aqidah morality is reviewed, particularly those that have been used at MTS Sunan Ampel Krejengan in the Probolinggo area.